2018
DOI: 10.1029/2018gc007729
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Carbonate Veins Within the Sedimentary Cover and Igneous Rocks of the Cocos Ridge: Results From IODP Hole U1414A

Abstract: Carbonate veins in the igneous basement and in the lithified sedimentary cover of the Cocos Ridge at International Ocean Discovery Program (IODP) Hole 344‐U1414A reveal the hydrologic system and fluid‐rock interactions. IODP Hole 344‐U1414A was drilled on the northern flank of the Cocos Ridge and is situated 1 km seaward from the Middle America Trench offshore Costa Rica. Isotopic and elemental compositions were analyzed to constrain the fluid source of the carbonate veins and to reveal the thermal history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 112 publications
(203 reference statements)
2
13
0
Order By: Relevance
“…Dissolved Ca in the infiltrating fluid would thereby be extracted before it reaches the mantle, and replacement of calcium silicates with calcium carbonates is possible if the Ca 2+ cation is scarce. This scenario is consistent with Brandstätter et al (), who found carbonate veins within upper‐basement drill cores on the Cocos Ridge, which we interpret as a relict track of the Galapagos hot spot. These chemical alterations within the plume track offer a pathway for large‐scale volatile transport into the deep mantle within the slab's cool interior, transported much later via subduction.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Dissolved Ca in the infiltrating fluid would thereby be extracted before it reaches the mantle, and replacement of calcium silicates with calcium carbonates is possible if the Ca 2+ cation is scarce. This scenario is consistent with Brandstätter et al (), who found carbonate veins within upper‐basement drill cores on the Cocos Ridge, which we interpret as a relict track of the Galapagos hot spot. These chemical alterations within the plume track offer a pathway for large‐scale volatile transport into the deep mantle within the slab's cool interior, transported much later via subduction.…”
Section: Discussionsupporting
confidence: 93%
“…With scarce olivine to serpentinize, and serpentinization reactions between pyroxene and seawater that are sluggish at lower temperatures (Bach et al, ), the oceanic crust undergoes negligible volume expansion and develops throughgoing crack networks that allow seawater access to the sub‐Moho peridotite. This crack scenario is a prediction for the oceanic crust, not an observation, but is nevertheless consistent with the crack topology described by Brandstätter et al () within the shallow crustal basement basalts of IODP Hole U1414A on the Cocos Ridge.…”
Section: The Thermodynamic Limits Of Metasomatic Underplatingsupporting
confidence: 91%
See 2 more Smart Citations
“…The volcanic units of the Izu-Bonin forearc and rear arc are substantially and similarly pervaded by veins that document extensive fluid flow through the oceanic crust and subsequent secondary mineral precipitation (Arculus, Ishizuka, Bogus, & the Expedition 351 Scientists, 2015;Christeson et al, 2016;Reagan et al, 2015). Numerous previous studies on calcite veins pervading the oceanic crust used δ 18 O, δ 13 C, and 87 Sr/ 86 Sr isotopic compositions, rare earth element and yttrium (REE+Y) concentrations, and fluid inclusions to investigate the geochemical composition of circulating fluids, and the age and temperature of secondary mineral precipitation (e.g., Alt & Teagle, 2003;Alt et al, 1998;Brandstätter et al, 2016;Brandstätter et al, 2018;Hart & Staudigel, 1978;Quandt et al, 2018;Quandt, Micheuz, Kurz, Kluge, et al, 2019;Schroeder et al, 2015). However, studies on calcite veins from the Izu-Bonin-Mariana trench in particular are rare.…”
Section: Introductionmentioning
confidence: 99%